2016
DOI: 10.3390/ijerph13050506
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors to Colorectal Cancer Screening among Chinese People: A Review of Quantitative Studies

Abstract: Colorectal cancer (CRC) is a major health problem in Asia. It has been reported that the Chinese are more susceptible to CRC than many other ethnic groups. Screening for CRC is a cost-effective prevention and control strategy; however, the screening rates among the Chinese are sub-optimal. We conducted a review to identify the factors associated with CRC screening participation among Chinese people. Twenty-two studies that examined the factors related to CRC screening behaviors among the Chinese were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 45 publications
2
28
1
Order By: Relevance
“…Patient at earlier stages had a significant improvement in survival. This finding underlines the importance of early diagnosis and increased awareness of CRC in China [34,35].…”
Section: Discussionmentioning
confidence: 53%
“…Patient at earlier stages had a significant improvement in survival. This finding underlines the importance of early diagnosis and increased awareness of CRC in China [34,35].…”
Section: Discussionmentioning
confidence: 53%
“…Regarding the low rates of CRC screening, some factors affecting participation like socio-demographic characteristics (educational level, health insurance, and knowledge of CRC and CRC screening), psychological factors (perceived severity of CRC, susceptibility to CRC, and barriers to screening), and contact with medical provider (physician recommendation) could be considered. [44] To improve participation in CRC screening in China, more studies are clearly needed to address these points including a longer follow-up of the present study, to better inform the citizens regarding the benefits of CRC screening.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few of the studies in this review examined screening test related factors, such as perceived screening effectiveness. Another recent review on Chinese adults also reported similar factors that influence CRC screening behavior [ 15 ]. As noted in this recent review, only a few of the reviewed studies utilizing current health theories to guide the inquiry.…”
Section: Introductionmentioning
confidence: 95%
“…Numerous systematic reviews of demographic, social, and environmental determinants of CRC screening have been produced in the last few decades [ 10 , 11 , 12 , 13 , 14 , 15 ]. The single systematic review of 83 studies focusing on people aged ≥65 revealed a number of demographic variables (educational level, race, ethnicity, gender, marital status, and living status) and health-care systems related variables (recommendation by physicians, having a usual source of care, and lack of health insurance) were important factors to the uptake of CRC screening tests [ 13 ].…”
Section: Introductionmentioning
confidence: 99%